2017
DOI: 10.1111/bdi.12540
|View full text |Cite
|
Sign up to set email alerts
|

Are patients with bipolar disorder and comorbid attention‐deficit hyperactivity disorder more neurocognitively impaired?

Abstract: Our results, although preliminary, suggest that the BD+ADHD group showed the same neurocognitive profile as pBD patients, most likely reflecting the same neurobiological basis. On the other hand, the pADHD group showed a more selective moderate impairment in attention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 50 publications
2
15
0
Order By: Relevance
“…There are few previous studies in this area. Our finding of small overall cognitive differences between BD-cADHD and BD + cADHD is largely in agreement with the results of Torres and colleagues (Torres et al 2017) who found no significant differences between BD and BD + ADHD. Another study (Silva et al 2014) used only the Wisconsin Card Sorting Test and found that BD + ADHD showed set-shifting difficulties compared with ADHD and healthy controls.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…There are few previous studies in this area. Our finding of small overall cognitive differences between BD-cADHD and BD + cADHD is largely in agreement with the results of Torres and colleagues (Torres et al 2017) who found no significant differences between BD and BD + ADHD. Another study (Silva et al 2014) used only the Wisconsin Card Sorting Test and found that BD + ADHD showed set-shifting difficulties compared with ADHD and healthy controls.…”
Section: Discussionsupporting
confidence: 93%
“…The accuracy of retrospective self-reports of childhood symptoms has been questioned (Barkley et al 2002; Mannuzza et al 2002), and it is considered best practice to include multiple sources of information, e.g., a parental or next of kin interview (Davidson 2008). Furthermore, replication is needed given the limited sample size in the previous study (Torres et al 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With one third, attention-deficit/hyperactivity disorder (ADHD) was the most frequent individual condition comorbid with BDspectrum disorders. This finding is consistent with some (Wingo and Ghaemi 2007;Torres et al 2017), but different from other studies conducted in adults where anxiety disorders (particularly panic attacks) were the most common comorbid diagnoses (Merikangas et al 2011).…”
Section: Comorbiditysupporting
confidence: 87%
“…The present study had no control group of healthy individuals, and the cognitive data were adjusted for different variables (age, sex and education, according to the published reference values for the cognitive tests). Another limitation was related to the fact that participants included in this study were not screened for attention-deficit hyperactivity disorder (ADHD) and were thus not excluded, although a recent study reported that individuals with BD and ADHD showed the same cognitive performance as individuals with BD alone (Torres et al , 2017). The idea that there is a single consensus threshold to define impairment in clinical practice is questionable: a clinically significant cognitive deficit may rely on contextual factors such as premorbid ability.…”
Section: Discussionmentioning
confidence: 99%